DNA-PKcs is critical for telomere capping - Gilley, David (The National Academy of Sciences, 2001)
The DNA-dependent protein kinase catalytic subunit (DNA-PKcs) is critical for DNA repair via the nonhomologous end joining pathway. Previously, it was reported that bone marrow cells and spontaneously transformed fibroblasts from SCID (severe combined immunodeficiency) mice have defects in telomere maintenance. The genetically defective SCID mouse arose spontaneously from its parental strain CB17. One known genomic alteration in SCID mice is a truncation of the extreme carboxyl terminus of DNA-PKcs, but other as yet unidentified alterations may also exist. We have used a defined system, the DNA-PKcs knockout mouse, to investigate specifically the role DNA-PKcs specifically plays in telomere maintenance. We report that primary mouse embryonic fibroblasts (MEFs) and primary cultured kidney cells from 6–8 month-old DNA-PKcs-deficient mice accumulate a large number of telomere fusions, yet still retain wild-type telomere length. Thus, the phenotype of this defect separates the two-telomere related phenotypes, capping, and length maintenance. DNA-PKcs-deficient MEFs also exhibit elevated levels of chromosome fragments and breaks, which correlate with increased telomere fusions. Based on the high levels of telomere fusions observed in DNA-PKcs deficient cells, we conclude that DNA-PKcs plays an important capping role at the mammalian telomere.